PERAN GURU NANAK DEV DAN PERKEMBANGAN AGAMA SIKH DI INDIA TAHUN 1499-1708 - Widi Andreliyani; Umi Hartati (Swarnadwipa, 2021)
The problem in this study is to analyze the role of Guru Nanak Dev and the development of the Sikh religion in India. The purpose of this study is to analyze and describe the role of Guru Nanak Dev in the field of religion in the effort to establish the Sikh religion, the development of Sikh religion in India and its impact. The research method uses historical research methods which are a review of various sources that contain information about the past and are carried out systematically. Based on the research results, the role of Guru Nanak Dev in establishing the Sikh religion in India, Guru Nanak Dev founded the Sikh religion with a great mission in his life. that is, to guide mankind to the right path. Guru Nanak Dev teaches universal love, high tolerance and views someone not from the level of caste because according to him all human beings on this Earth are born the same without any difference whatsoever. Guru Nanak Dev always actively spreads his teachings even though he has to go through various obstacles and obstacles. Guru Nanak Dev managed to attract many followers to follow the teachings he had brought because the way he taught his teachings was so simple and practical that it could touch the human conscience. Sikhs believe in and follow ten Guru namely Guru Nanak Dev, Guru Angarh, Guru Amar Das, Guru Ram Das, Guru Arjuna, Guru Har Gobind, Guru Har Rai Singh, Guru Hari Krishen, Guru Tegh Baharudin, and Guru Govind Singh who are very great role in the history of the spread and development of Sikh religion in India. The rapid development of the Sikh religion in India has also caused it to spread to all regions of the World.